TOSSH: A Toolbox for Streamflow Signatures in Hydrology. (April 2021) - Gnann, Sebastian J.; Coxon, Gemma; Woods, Ross A.; Howden, Nicholas J.K.; McMillan, Hilary K.
Abstract: We present a Matlab toolbox to calculate hydrologic signatures, which are metrics that quantify streamflow dynamics. Signatures are widely used for catchment characterisation, hydrologic model evaluation, and assessment of instream habitat, but standardisation across applications and advice on signature selection is lacking. The toolbox provides accessible, standardised signature calculations, with clear information on methodological decisions and recommended parameter values. The toolbox implements three categories of signatures: basic signatures that describe the five components of a natural streamflow regime, signatures from benchmark papers, and an extended set of process-based signatures. The toolbox is designed for ease of use, including documentation, workflow scripts and example data to demonstrate implementation procedures, and visualisation options. We demonstrate the accuracy and robustness of the signature calculations by applying reproducible workflows to large streamflow datasets. The modular design of the toolbox allows for flexibility and easy future expansion. The toolbox is available from https://github.com/TOSSHtoolbox/TOSSH (https://doi.org/10.5281/zenodo.4313275 ). Highlights: We present a Matlab toolbox to calculate hydrologic signatures, which are metrics that quantify streamflow dynamics. The toolbox provides accessible, standardised signature calculations, with clear information on methodological decisions. We demonstrate the accuracy and robustness of the toolbox by applying reproducible workflows to large streamflow datasets.